Influence Of Leadersa Perceived Power Source On Nigeria Surbodinate Employeesa Commitment And Work Attitude (Global Journal of Human-Social Science, 2012)
The study examined the influence of leaders' perceived power source on subordinate employees' commitment and work attitude. One hundred and eighty-three (183) respondents completed a questionnaire comprising of the Power Source Scale, Organizational Commitment Scale and the Work Group Functioning Scale. The research participants were selected in Ado Ekiti, Nigeria metropolis through a multi level random sampling method. Responses from the survey research were analysed using the multiple regression analysis, the independent t test, and the Pearson correlation analysis. Results of the study showed that leaders' perceived power source had a significant influence on employees' commitment and work attitude. A positive relationship was also found to exist between leaders' perceived power source and employees' commitment, and between work attitude and employees commitment. No significant relationship existed, however, between leaders' perceived power source and work attitude. It was also revealed that sex of employees had no significant effect on employees' commitment and work attitude.
Keywords: Perceived Power Source; Work Attitude; Employees2019; Commitment; Nigeria